ANALISIS KELAYAKAN LEMBAR KERJA SISWA IPS KELAS IX BERDASARKAN STANDAR BSKAP PADA IMPLEMENTASI KURIKULUM MERDEKA - Shifni Azkiya; Noviani Achmad Putri (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
This study aims to analyze the feasibility of the Grade IX Social Studies Student Worksheet (LKS) produced by the Social Studies Teacher Working Group (MGMP IPS) of Tegal City, which is uniformly used across all public junior high schools in Tegal City during the odd semester of the 2025/2026 academic year. A descriptive quantitative approach with document analysis method was employed to assess all 112 pages of the LKS based on four standards of the BSKAP Educational Book Assessment Guidelines Number 039/H/P/2022, namely content, presentation, design, and graphics. As supporting data, a Likert scale questionnaire was administered to 113 ninth-grade students of SMP Negeri 7 Tegal, obtained through convenience sampling from a population of 239 students. Document analysis results show an overall percentage of 70.3% (feasible), with details of content standard 66.7% (moderately feasible), presentation 68.75% (moderately feasible), design 58.3% (moderately feasible), and graphics 91.7% (highly feasible). The student questionnaire yielded a percentage of 77.1% (feasible). Key weaknesses identified include outdated real-world examples, the absence of QR codes, dominance of lower-order cognitive questions, writing errors, and minimal visual elements on core content pages. This study affirms the need for periodic evaluation of teacher-community-produced worksheets to ensure alignment with the demands of the Merdeka Curriculum. ABSTRAK Penelitian ini bertujuan menganalisis kelayakan Lembar Kerja Siswa (LKS) IPS Kelas IX buatan MGMP IPS Kota Tegal yang digunakan di seluruh SMP Negeri se-Kota Tegal pada semester gasal tahun ajaran 2025/2026. Pendekatan kuantitatif deskriptif dengan metode analisis dokumen digunakan untuk menilai 112 halaman LKS berdasarkan empat standar Pedoman Penilaian Buku Pendidikan BSKAP Nomor 039/H/P/2022, yaitu materi, penyajian, desain, dan grafika. Sebagai data pendukung, kuesioner skala Likert diberikan kepada 113 siswa kelas IX SMP Negeri 7 Tegal yang diperoleh melalui teknik convenience sampling dari populasi 239 siswa. Hasil analisis dokumen menunjukkan persentase keseluruhan 70,3% (layak), dengan rincian standar materi 66,7% (cukup layak), penyajian 68,75% (cukup layak), desain 58,3% (cukup layak), dan grafika 91,7% (sangat layak). Kuesioner siswa menunjukkan persentase 77,1% (layak). Kelemahan utama meliputi contoh nyata yang belum diperbarui, ketiadaan kode QR, dominasi soal kognitif rendah, kesalahan tata tulis, dan minimnya elemen visual. Penelitian ini menegaskan perlunya evaluasi berkala terhadap LKS buatan komunitas guru agar selaras dengan tuntutan Kurikulum Merdeka.